UPAYA MENURUNKAN JAJANAN TIDAK SEHAT PADA ANAK USIA DINI KELOMPOK B3 MELALUI KOLABORASI ORANG TUA DAN GURU DI RA DARUSSALAM - Elianti Wijaya; Abdul Muiz Rouf; Muhammad Azka Maulana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The consumption of unhealthy snacks among young children is a serious issue that can disrupt health, growth, and learning concentration. This study aims to describe efforts to reduce the consumption of unhealthy snacks through collaboration between parents and teachers at RA Darussalam. This research used an action research method with a qualitative approach. Data were collected through participatory observation, in-depth interviews with teachers and parents, and documentation studies. The research subjects were 18 children from group B3, their parents, and teachers at RA Darussalam. The results showed that collaboration between parents and teachers was formed through regular communication, joint educational activities (such as "Healthy Friday"), and agreements prohibiting unhealthy snacks. This collaboration was effective in increasing parental awareness and active participation (98.5%) and the role of teachers (79.3%) in habituating healthy food consumption. However, its effectiveness was still constrained by a less supportive school environment (61.5%), such as the ongoing sale of unhealthy snacks in the canteen and limited nutritional education media. The study concludes that parent-teacher collaboration is an effective strategy for reducing unhealthy snack consumption but requires optimal environmental support and consistent commitment from all parties. It is recommended that schools improve supervision and support facilities, parents increase consistency at home, and future researchers develop digital parenting modules for more sustainable collaboration.